THE EFFORTS TO OVERCOME THE DIFFICULTIES OF LEARNING ARABIC IN MTs. YASRIB LAPAJUNG BOARDING SCHOOL - Syamsudar Syamsudar (JICSA : Journal of Islamic Civilization in Southeast Asian, 2019)
This study aimed: 1) to describe the learning process in MTs. Yasrib Lapajung Boarding School, 2) To reveal the kind of difficulties in learning Arabic in MTs. Yasrib Lapajung Boarding School, 4) To describe the efforts done by Arabic teachers in overcoming the difficulties of learning Arabic in MTs. Yasrib Lapajung Boarding School. This research was descriptive qualitative by analyzing and describing the data in an objective and detailed manner to obtain accurate results. The data sources of this study were from the headmaster, Arabic teachers, and the students of MTs. Yasrib Lapajung Boarding School as informants. The technique of data collection was done by conducting interview, observation, and documentation. Data processing technique and qualitative analysis used three stages, namely: 1) data reduction, 2) data display, and 3) conclusion. The results showed that; first, the process of learning Arabic in MTs. Yasrib Lapajung Boarding School was divided into three parts, they were learning plan, implementation, and evaluation. Second, the students' difficulties that emerged in learning Arabic, namely: istima' (listening), kalam (speaking), qira'ah (reading), and kitabah (writing). Third, to overcome the learning difficulties that existed in learning Arabic related to difficulties in aspects of language skills, the teacher asked the students to memorize mufradat (vocabulary) and translate a sentence, to write Arabic by dictation (imla'), and to practice conversation so that the students were accustomed in speaking Arabic, the teacher also fostered the students' motivation and interest, and held extracurricular activities.